'Blocked' Youth: The Politics of Migration from South and East Mediterranean Countries Before and After the Arab Uprisings. Issue 2 (3rd April 2018) - De Bel-Air, Françoise
Abstract: Migration from South and East Mediterranean (SEM) countries has been considered a growing security threat in the EU and Gulf states following the 9/11 attacks and the Arab uprisings. Since 2011, the economic slowdown, regime changes and socio-political instability have spurred growing migration pressure from SEM countries. However, the securitisation of migration of young citizens from these countries in the EU and the Gulf states is manifested in the drastic limitation of migrants' inflows, and in the selection of prospective migrants on demographic, socio-economic and political grounds. Today's 'governmentality' of youth migration from SEM countries poses ethical and development-related issues.